A gate driver for IGBT with data acquisition function - YANG Lele; CHEN Yanping; DOU Zechun; QI Yu; XIE Shunmeng; WE Haishan (机车电传动)
The paper presents a new type of gate driver for IGBT, which has the function of acquiring the operation state data in addition to traditional gate drive and short-circuit protection functions. Acquiring data of IGBT in normal operation state and at fault is conducive to understanding the working environment of IGBT, analyzing IGBT failure mechanism, and providing theoretical basis for the improvement and positive design of power electronic devices in power system. The gate driver is based on field programmable gate array, which integrates pulse control, drive and protection, signal acquisition, and serial communication functions. The main functional modules are described in detail in the paper, and the functions and reliability were verified by mathematical model simulation and experiments. The paper provides a technical reserve for the digital and intelligent development of gate drive technology, and data support for the failure analysis and health management research of IGBT modules.